SUMBANGAN MIKROBA PELARUF FOSFAT INDEGENUS TERHADAP PENINGKATAN PRODUKTIVITAS LAHAN PERTANIAN DI PROVINSI RIAU - Ida Nur Istina; Nurhayati Nurhayati; Jakoni Jakoni (UIR Press, 2019)
ABSTRACT The obstacle to agricultural development in peatlands is the low nutrient content needed for plant growth. One effort that can be done to increase agricultural productivity in peatlands is a friendly environmental fertilization. This research aims to find out the role of indigenous phosphate solubilizing microbes in enhanced peat soil fertility in Kampar District in 2014 by using a Factorial Randomized Block Design with 3 replications. First factor was MPF inoculation (control; Burkholderia gladioli and penicillium aculeatum), and the second factor was Ameliorants (Control, Oil Palm Empty Fruit Bunch (TKKS) Compost, 4 kg TKKS compost/polybag and 25% recommended dosage, 4 kg TKKS compost/polybag and 50% recommended dosage, 4 kg TKKS compost/polybag and 75% recommended dosage, 4 kg TKKS compost/polybag and 100% P recommended dosage. Soil Nutrient analyses carried out at the laboratories of Vegetable Crops Research Institute Lembang. The parameters observed were: soil content of nutrients N, P, K, Ca, and Mg. The results showed that the indigenous phosphate solubilizing microbe increased the soil's nutrient content.